Kejahatan Nama Domain Berkaitan dengan Merek - Muhammad Nizar (Universitas Airlangga, 2018)
Indonesia already has an ITE Law governing domain names in general terms and on certain provisions in chapter VI, but the regulation of domain name crimes is not regulated in the ITE Law as mandated in the academic draft of the ITE Bill. The absence of regulation of domain name norm in the ITE Law creates problems with registrant of domain name (registrant) which deliberately register the domain name is bad faith. The characteristic of a crime in a domain name relating to the mark is that the registered domain name has an equation in essence with another party’s well-known brand, the act of doing so by exploiting a reputation for well-known or previously commercially valuable names as domain names for addresses for sites (websites) it manages. The Prosecutor may include articles of the KUHP in filing his indictment before the Court during the absence of special regulatory provisions concerning domain name crime.